A boosted negative bit-line SRAM with write-assisted cell in 45 nm CMOS technology. (February 2018) - Bhatnagar, Vipul; Kumar, Pradeep; Pandey, Neeta; Pandey, Sujata
Abstract: A new 11 T SRAM cell with write-assist is proposed to improve operation at low supply voltage. In this technique, a negative bit-line voltage is applied to one of the write bit-lines, while a boosted voltage is applied to the other write bit-line where transmission gate access is used in proposed 11 T cell. Supply voltage to one of the inverters is interrupted to weaken the feedback. Improved write feature is attributed to strengthened write access devices and weakened feedback loop of cell at the same time. Amount of boosting required for write performance improvement is also reduced due to feedback weakening, solving the persistent problem of half-selected cells and reliability reduction of access devices with the other suggested boosted and negative bit-line techniques. The proposed design improves write time by 79%, 63% and slower by 52% with respect to LP 10 T, WRE 8 T and 6 T cells respectively. It is found that write margin for the proposed cell is improved by about 4×, 2.4× and 5.37× compared to WRE8 T, LP10 T and 6 T respectively. The proposed cell with boosted negative bit line (BNBL) provides 47%, 31%, and 68.4% improvement in write margin with respect to no write-assist, negative bit line (NBL) and boosted bit line (BBL) write-assist respectively. Also, new sensing circuit with replica bit-line is proposed to give a more precise timing of applying boosted voltages for improved results. All simulations are done on TSMC 45 nm CMOS technology.